DESIGN AND EVALUATION OF A MOOC FOR CLINICAL EDUCATORS (Proceedings of the International Conference on Education, 2021)
The MOOCs offer education with high quality standards and have the potential to offer better educational experiences within learning communities where students and teachers from multiple institutions and areas participate. Clinical professors need to be continuously trained with new alternatives that reduce the gap of traditional education with the needs of students. In addition, it is essential to move from education focused exclusively on science, towards a comprehensive education focused on the needs of the most important actor: the patient. The purpose was to design, implement, and evaluate a MOOC on educational evaluation in health sciences. The content of the MOOC was designed and developed with the participation of 15 professors from three universities in Mexico. A pilot was implemented during September-October 2019 to train at least 30 teachers from the three universities. An instrument was designed to measure the fulfillment of teachers' expectations. The pre-test was applied before starting the pilot course and the post-test at the end of the program. The tests were answered by 29 of 57 professors, whose data were analyzed using the t-student statistical test. The course was successfully completed by 33 of 57 teachers. The results of the statistical test show that there is a significant difference. The expectations of the teachers who completed the course were exceeded. For the educational proposal to be considered valuable, it must consistently meet the participant's learning needs according to the effort and cost invested. Knowing the perceived value indicates how participants conceive the value of the program. In this sense, MOOCs represent opportunities for teacher training in educational evaluation. The project has great potential for impact at the Latin American level.
Keywords: MOOC; clinical teachers; health sciences; clinical competence; patient-centered learning; educational innovation